Novel marrellomorph moulting behaviour preserved in the Lower Ordovician Fezouata Shale, Morocco - Drage, Harriet B.; Legg, David A.; Daley, Allison C. (Frontiers in Ecology and Evolution, 2023)
Exoskeleton moulting is the process of shedding the old exoskeleton to enable growth, development and repair, representing a crucial recurrent event in the life histories of all euarthropods. The fossil record of moulting allows us to interpret the evolution of this important behaviour and its impact on the evolutionary trajectories of extinct and extant euarthropods. Current knowledge of Palaeozoic euarthropod moulting relates largely to trilobites, with fewer examples known for non-mineralised extinct taxa from early in euarthropod evolutionary history. We describe exuviae from a marrellid marrellomorph found abundantly in the Early Ordovician Fezouata Shale lagerstätte of Morocco, which allow a novel reconstruction, the second ever, of marrellid moulting behaviours. We identify the moulting suture location, describe preserved moulting assemblages, and suggest how its moulting behaviours are adaptive to its morphology. Several specimens represent complete and nearly complete assemblages and additional disarticulated specimens confirm the suture line location. The suture line is located between the mediolateral and posterolateral spine pairs, dividing the cephalic shield into anterior and posterior parts. The Fezouata marrellid likely exited the exoskeleton during exuviation using posterior and upwards movements, analogous in terms of movement to lobster-like extant arthropods. The suture line is comparable in the closely related marrellid Mimetaster, and distinctive from that of another marrellid, Marrella splendens, which has an exuvial opening at the anterior of the cephalic shield and exited the exoskeleton anteriorly. This difference in moulting behaviour as compared to Marrella is likely adaptive to the greater complexity of the Fezouata marrellid, with upwards rather than forwards movement presumably providing a more favourable angle for the extraction of complex spines. This description of the moulting behaviours and related morphological features of marrellomorphs expands our understanding of this crucial characteristic in extinct euarthropods.